Mechanical and thermal properties of rubber toughened polyester filled carbon black (cb) and kenaf hybrid composite / Aein Afina Mohd Redzuan - Mohd Redzuan, Aein Afina (2017)
This study was conducted to investigate the mechanical and thermal properties which are flexural strength, flexural modulus, impact strength, fracture toughness, storage modulus, tan delta, curing behaviour, decomposition temperature, glass transition temperature, followed by chemical interaction and morphological properties of rubber toughened composites. Neat polyester, rubber toughened polyester (RP), rubber toughened polyester composite filled carbon black (RPCB), rubber toughened polyester filled CB and treated kenaf (RPCBTK) and rubber toughened polyester filled CB and untreated kenaf (RPCBUK) hybrid composite were produced.